Smart applications for diabetes management: A comprehensive survey and ranking. (June 2020) - Ubaid Ur Rehman, Muhammad; Aleem, Muhammad; Islam, Muhammad Arshad; Ahmed, Salman
Diabetes is a chronic disease, and its treatment requires intensive management of medication, diet, and exercise. Nowadays, information and communication technology provides diverse facilities to patients and medical specialists to manage different diseases in an efficient manner with the help of smartphone technology. Earlier studies have not ranked diabetes management apps by correlating each app feature, and their review is not comprehensive. Therefore, this study presents a comprehensive analysis of the existing diabetes-related smartphone applications. Moreover, we examine the factors based on which most of the users provide a higher rank to a particular application. We classify the diabetes mobile applications with respect to the application features and perform rigorous analysis of the top 15 applications. The results indicate that there exists a weak correlation between the number of downloads and user ratings. For evaluation, we calculate the normalized discounted cumulative gain score to rank applications based on its features. The results demonstrate that a higher normalized discounted cumulative gain score is attained by those mobile applications that contain the data-sharing feature.